Exploring the effect of guest experience on guest loyalty: Mediating role of guest satisfaction - Filda Rahmiati; Putu Gede Lila Gargamunih Dewi; Norfaridatul Akmaliah Othman; Ketwadee Madden; Geraldine B. Advincula; Yohana Sitorus (Universitas Ahmad Dahlan, 2024)
Indonesia is known as an archipelago of islands with a wide variety of cultures and natural beauty, providing many options for tourists to visit. This research aims to investigate the influence of guest experiences on guest loyalty within the accommodation sector, focusing on Indonesian Generation Z. The study employs a quantitative method, utilizing an online survey distributed through Google Forms, to gather data from 146 valid respondents who had stayed in Indonesian accommodations within a year. The data was processed using partial least squares structural equation modeling with Smart PLS 3.2.9. The results reveal that guest experiences in pre-trip, on-trip, and post-trip directly influence guest satisfaction. Guest satisfaction significantly influences guest loyalty. Moreover, guest loyalty is indirectly influenced by guest experiences (in pre-trip, on-trip, and post-trip) that are mediated by guest satisfaction. Guest experiences in pre-trip, on-trip, and post-trip have no direct influence towards guest loyalty. These findings highlight the importance of providing excellent services and products before, during, and after the trip to increase guest loyalty through guest satisfaction. The results contribute to the development of effective strategies for enhancing guest loyalty and satisfaction, ultimately benefiting accommodation providers and the broader hospitality industry.